Efficient chemoenzymatic valorization of biobased D-fructose into 2, 5-bis(hydroxymethyl)furan with deep eutectic solvent Lactic acid:Betaine and Pseudomonas putida S12 whole cells. (January 2022) - Zhang, Shunli; Ma, Cuiluan; Li, Qi; Li, Qing; He, Yu-Cai
Graphical abstract: Highlights: Carboxylic acid in deep eutectic solvent affected D -fructose dehydration activity. Yield of 5-HMF reached 91.6% in Lactic acid:Betaine − H2 O (15:85, v:v) at 150 °C. D -Fructose-derived 5-HMF was bioconverted to 2, 5-bis(hydroxymethyl)furan at 98% yield. Chemoenzymatic catalysis of D -fructose to 2, 5-bis(hydroxymethyl)furan was developed. Abstract: 2, 5-Bis(hydroxymethyl)furan (BHMF) is one kind of important upgraded derivatives of biobased 5-hydroxymethylfuran (5-HMF). This study verified the feasibility of one-pot chemoenzymatic conversion of biobased D -fructose to BHMF by cascade catalysis with deep eutectic solvent Lactic acid:Betaine (LA:B) and reductase biocatalyst in LA:B − H2 O. Using D -fructose (36.0 g/L) as feedstock, the yield of 5-HMF reached 91.6% in DES LA:B − H2 O (15:85, v:v) at 150 °C for 1.5 h. Using D -fructose (2 mol D -fructose/mol 5-HMF) as cosubstrate, commercial 5-HMF (125 mM) was converted into BHMF at 90.7% yield by whole-cells of Pseudomonas putida S12 within 24 h at 30 °C and pH 8.0. In addition, Pseudomonas Putida S12 could efficiently transform D -fructose-valorized 5-HMF into BHMF [98.4% yield, based on 5-HMF; 90.1% yield, based on substrate D -fructose] in DES LA:B − H2 O. An efficient chemoenzymatic valorization of D -fructose to BHMF was developed in a benign reaction system.